Spelling errors in interlingual subtitles: do viewers really mind? - Deckert, Mikołaj (Penerbit Universiti Kebangsaan Malaysia, 2021)
Our overarching objective is to see how unambiguous deficiencies in interlingual subtitles influence the viewing experience. To that end, we conducted a reception experiment in which participants viewed a foreign language film sample with subtitles which were manipulated across conditions for the number of spelling errors. We find that while viewers succeed in identifying spelling errors in subtitles, the presence of errors nonetheless generally has no effect on a range of viewer experience dimension like cognitive load, enjoyment, comprehension or transportation. What is more, while participants were able to make different subtitle authorship attributions (professional subtitler vs. amateur subtitler) depending on the presence of typos, deficient spelling did not shape the viewer’s perception of the subtitler in terms of their estimated amount of experience or their diligence. Critically, the findings also indicate that typos have no effect on translation quality assessment scores which remain high even when there are as many as 20 typos in subtitles for a 14-minute clip. This work therefore offers new insights into translation reception with consequences for the didactic and professional settings. By embedding spelling errors in a dynamic and multimodal context where processing is not self-paced, the study importantly expands our understanding of how spelling errors are received, which has implications beyond translation studies as well.